Influence of cutter diameter on meshing performance in spiral bevel gears - Ma, Zhi-hao; Han, Xing-hui; Hua, Lin; Xiong, Xiao-shuang; Zheng, Fang-yan (Journal of Central South University, 2016)
Playing a critical role in transmitting movement and power, the meshing performance of spiral bevel gears has a significant effect on products’ operational performance. To evaluate the meshing performance, the accurate three-dimensional (3D) spiral bevel gear models are established through the Pro/E and MATLAB softwares, and the finite element analysis (FEA) methods are applied to the theoretical investigation of the influence of cutter diameter on meshing performance in spiral bevel gears. The results obtained show that the cutter diameter has a significant influence on spiral bevel gears’ meshing performance, such as the contact area, contact pressure, bending stress, torsional stiffness and transmission error.